Dietary patterns and respiratory symptoms in pre-school children: the Generation R Study - Ilse I.M. Tromp; Jessica C. Kiefte‐de Jong; J.H.M. de Vries; Vincent W. V. Jaddoe; Hein Raat; Albert Hofman; Johan C. de Jongste; Henriëtte A. Moll (2012)
Overall diet in early childhood may affect the development of respiratory symptoms. This study examined whether childhood dietary patterns are associated with respiratory symptoms in Dutch pre-school children, and whether this association could be explained by energy intake. A prospective cohort study was performed in 2,173 children aged ≤4 yrs. Data on asthma-related symptoms were obtained by questions from the age-adapted version of the "International Study of Asthma and Allergies in Childhood" questionnaires. Data on respiratory tract infections, defined as episodes of physician attended fever with respiratory symptoms, was obtained by questionnaire. Principal components analysis was used to develop dietary patterns at 14 months of age. Compared with low adherence, high adherence to the “Western” dietary pattern was significantly associated with frequent wheeze at 3 yrs of age (relative risk (RR) 1.39, 95% CI 1.02–1.89) and frequent shortness of breath (RR 1.44, 95% CI 1.03–2.01) and respiratory tract infections (RR 1.54, 95% CI 1.08–2.19) at 4 yrs of age. However, this association was partially explained by energy intake. A “Western” diet may increase the risk of frequent respiratory symptoms at 3 and 4 yrs of age. In some measure, this association was explained by energy intake.